Preventive and Therapeutic Effects of Astaxanthin on Depressive-Like Behaviors in High-Fat Diet and Streptozotocin-Treated Rats - Ke, Yuting; Bu, Shizhong; Ma, Hong; Gao, Lei; Cai, Yujia; Zhang, Yisheng; Zhou, Wenhua (Frontiers in Pharmacology, 2020)
The comorbidity of diabetes and depression has a negative impact on both lifestyle and quality of life. Astaxanthin (AST) has been demonstrated to improve glucose metabolism and has antidepressant-like effects, but it is not clear whether AST has potential for preventing depression in diabetes. The aim of this study is to observe the preventive and therapeutic effects of AST on glucose metabolism or depressive-like behaviors in a diabetic rat model produced by feeding with a high-fat diet for 10 weeks followed by injection of 25 mg/kg streptozotocin (STZ). Preventive treatment with AST at doses of 7.5, 15, and 25 mg/kg/day was given by intragastric gavage 4 weeks before STZ injection. Preventive plus therapeutic treatment also involved therapeutic AST treatments for 6 more weeks after STZ injection, whereas therapeutic-only treatment involved only the 6-week post-STZ treatment. Depressive-like behaviors were evaluated at the end of the treatment by using open field, locomotor activity, elevated plus maze, and forced swimming tests. Preventive and therapeutic treatment with AST both reduced the level of fasting glucose, improved glucose tolerance, and decreased total TCh and TG in diabetic rats. Preventive or preventative plus therapeutic treatment with AST decreased the immobility time and increased the time spent in the open arms of an elevated plus maze and locomotor activity in diabetic rats. However, therapeutic treatment with AST alone failed to affect the depressive-like behaviors. Preventive or preventative plus therapeutic treatment with AST at doses of 15 or 25 mg/kg significantly increased the expression of pERK, pAKT, pCREB, and BDNF in the prefrontal cortex (PFC) in diabetic rats. In contrast, therapeutic treatment with 25 mg/kg AST alone increased the expression of pERK in the PFC. This study indicates that AST may be used as a preventive or therapeutic approach for co-morbidity of diabetes and depression.